STUDENTS’ SPEAKING ANXIETY IN SPEAKING PERFORMANCE CLASS - Ayu Saharani (JOLE (Journal of Language Education), 2023)
Basically most students experience anxiety when making presentations in front of the classor speaking in front of many people. This anxiety can affect the learning process and also theresults of student learning. In this study, the authors aim to find the most dominant causes ofstudents' anxiety in speaking performance in front of the class or during presentations. Thedesign of this research used descriptive qualitative and the method is theoretical and libraryresearch methods. Based on several previous articles, the researcher found that one of themost dominant factors of anxiety experienced by students was due to their own negativethoughts which were afraid of the response from the audience. For the conclusion, theresearcher found several factors that influence students' anxiety in speaking or presenting inclass and also several strategies to control this anxiety. And the researcher also suggests tothe teacher concerned to help students to overcome this anxiety